Brucella mediates autophagy, inflammation, and apoptosis to escape host killing - Qin, Yaqiong; Zhou, Gengxu; Jiao, Fengyuan; Cheng, Chuan; Meng, Chi; Wang, Lingjie; Wu, Shengping; Fan, Cailiang; Li, Jixiang (Frontiers in Cellular and Infection Microbiology, 2024)
Brucellosis is a serious zoonosis caused by Brucella spp. infection, which not only seriously jeopardizes the health of humans and mammals, but also causes huge economic losses to the livestock industry. Brucella is a Gram-negative intracellular bacterium that relies primarily on its virulence factors and a variety of evolved survival strategies to replicate and proliferate within cells. Currently, the mechanisms of autophagy, inflammation, and apoptosis in Brucella-infected hosts are not fully understood and require further research and discussion. This review focuses on the relationship between Brucella and autophagy, inflammation, and apoptosis to provide the scientific basis for revealing the pathogenesis of Brucella.